Peningkatan Proses Pembelajaran Konsep Gerak Tumbuhan Melalui Model Pembelajaran Langsung - Rosmawati, Rosmawati (Indonesian Journal of Educational Studies, 2016)
This study aims to improve the learning process Biology class VIII SMP Negeri 1 Makassar through direct learning model on the concept of motion in plants. The study was designed with classroom action research. Subjects of this study consisted of 43 people. The data collection technique uses observation sheets and multiple choice tests given at the end of each cycle. Based on the analysis of qualitative data is concluded that there are some changes; (1) students showed enthusiasm to follow the lesson; (2) interest and motivation to learn biology students has increased; (3) the courage of expression, answering questions, responses, ask rise; (4) more optimistic / confidence in their abilities. Quantitatively, there is an increased score completeness of student learning outcomes very low category with a score of 44, 12% on the implementation of the first cycle into high category with a score of 70, 59% after the implementation of the second cycle